Effect of cooking methods on glycemic index and in vitro bioaccessibility of potato (Solanum tuberosum L.) carbohydrates. (June 2020) - Singh, Abhilasha; Raigond, Pinky; Lal, Milan Kumar; Singh, Brajesh; Thakur, Nitasha; Changan, Sushil S.; Kumar, Dharmendra; Dutt, Som
Abstract: Though potato is popular among masses as a carbohydrate rich source of energy, bioaccessibility studies of potato carbohydrates are never carried out. We investigated effect of cooking on glycemic index (GI) and in-vitro bioaccessibility in potato varieties Kufri Chipsona-3 and Lady Rosetta. Samples were analysed in raw, boiled, microwaved and fried form. On average, starch content significantly reduced by 40%, 64% and 2%; amylose by 14%, 17% and 34% after boiling, microwaving and frying, respectively. Total soluble sugars increased concomitantly by 9% and 25% in boiled and microwaved tubers and reduced by 10% in fried tubers. GI of boiled, microwaved and fried tubers of both the varieties was high i.e above 70. Starch content of both the varieties decreased during in-vitro digestion and was least in intestinal phase. Among the cooking methods, frying was better as reducing sugars remained low throughout oral, gastric and intestinal phases in both the varieties. Raw tubers of both varieties released maximum concentration of sugars during gastric phase. Whereas, boiled, microwaved and fried tubers of both the varieties released maximum concentration of sugars during intestinal phase. This study indicated that cooking method has significant effect on starch breakdown and release of sugars in the body. Highlights: Cooking methods significantly influences release of sugars in in-vitro gut model. Trend of release of sugars differed in raw and cooked potatoes in in vitro gut. Fried potatoes released least content of sugars throughout in-vitro gut. Starch hydrolysis and sugar release was maximum in microwaved potatoes. Resistant starch was high in fried compared to boiled and microwaved potatoes.